1995
DOI: 10.1159/000227516
|View full text |Cite
|
Sign up to set email alerts
|

5-Fluorouracil and <i>d, </i><i>l</i>-Leucovorin Calcium Are Active to Treat Unresectable Hepatocellular Carcinoma Patients: Preliminary Results of a Phase II Study

Abstract: Twenty-five patients affected with unresectable hepatocellular carcinomas (HCCs) were treated with 370 mg/m2 5-fluorouracil (5-FU) plus 200 mg/m2 racemic leucovorin both for 5 consecutive days. The chemotherapy cycle was repeated every 4 weeks until disease progression. One complete remission (4%) and 6 partial responses (24%) were obtained, that is 7 objective responses in all (28%, ninety-five confidence interval: 10.1–45.9%). All responders had a good PS and only 1 of them presented wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 9 publications
(12 reference statements)
4
18
0
Order By: Relevance
“…A phase II study of 5-FU combined with leucovorin showed modest activity with 28% response rates in advanced HCC (13). However, another phase II study of 5-FU with leucovorin showed poor clinical response with only 1 partial response (7%) (14).…”
Section: -Fluorouracil (5-fu)mentioning
confidence: 99%
“…A phase II study of 5-FU combined with leucovorin showed modest activity with 28% response rates in advanced HCC (13). However, another phase II study of 5-FU with leucovorin showed poor clinical response with only 1 partial response (7%) (14).…”
Section: -Fluorouracil (5-fu)mentioning
confidence: 99%
“…Therefore, combination therapy is considered to be more effective than monotherapy. There have been various combination chemotherapy in treating advanced HCC [8,9,11,12,22,23] or other malignancies [24]. Combination of etoposide, doxorubicin, cisplatin, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Various schedules and dose intensities of 5-FU (F) have been studied [4][5][6]. Biochemical modulation of 5-FU by leucovorin (L) has been found to enhance 5-FU-induced cytotoxicity and clinical effects [7][8][9]. Cisplatin and 5-FU (PF) are synergistic in vitro [10], and PF chemotherapy has resulted in a favorable response in advanced HCC [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Response rates w i t h 5 -F U m o n o t h e r a p y h a v e b e e n l o w . H o w e v e r , w h e n g i v e n i n c o m b i n a t i o n w i t h leucovorin, response rates as high as 28 percent have been reported (Porta et al, 1995).…”
Section: Fluoropyrimidinesmentioning
confidence: 99%